2020
DOI: 10.1021/acsomega.9b02498
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Colorimetry Properties of Transparent Wood Prepared from Six Wood Species

Abstract: Transparent wood (TW) was prepared by directly impregnating the wood cell wall and cavity with index-matched prepolymerized methyl methacrylate (MMA). In this process, lignin is retained compared with the preparation of transparent wood in the past, making the production faster and more energy-efficient. The innovation lies in that the prepared transparent wood retains the natural color and texture of the wood while transmitting light, especially under the illumination of a specific light source, which exist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 19 publications
(30 reference statements)
0
36
0
Order By: Relevance
“…As shown in Figure 3 b, the characteristic absorption peaks exhibited by NW are the same as those in the existing literature, including absorption peaks at 3375 cm –1 (O–H stretching vibration), 2925 cm –1 (C–H stretching vibration), 1736 cm –1 (C=O stretching vibration), 1505 and 1593 cm –1 (aromatic nucleus skeleton vibration), 1242 cm –1 (C–O stretching vibration), and 1034 cm –1 (ether bond vibration). 21 From the infrared spectra of five types of SW in Figure 3 b, it can be seen that the main stretching vibration point of SW in the spectrum is basically the same as NW, but the characteristic absorption peaks at 1736 cm –1 representing hemicellulose acetyl groups and the characteristic absorption peak strengths of lignin at 1593 and 1505 cm –1 were significantly reduced. This is because during the softening process, the hydrogen bond and ether linkage between lignin and hemicellulose was broken, which caused some lignin and hemicellulose to be dissolved and removed.…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure 3 b, the characteristic absorption peaks exhibited by NW are the same as those in the existing literature, including absorption peaks at 3375 cm –1 (O–H stretching vibration), 2925 cm –1 (C–H stretching vibration), 1736 cm –1 (C=O stretching vibration), 1505 and 1593 cm –1 (aromatic nucleus skeleton vibration), 1242 cm –1 (C–O stretching vibration), and 1034 cm –1 (ether bond vibration). 21 From the infrared spectra of five types of SW in Figure 3 b, it can be seen that the main stretching vibration point of SW in the spectrum is basically the same as NW, but the characteristic absorption peaks at 1736 cm –1 representing hemicellulose acetyl groups and the characteristic absorption peak strengths of lignin at 1593 and 1505 cm –1 were significantly reduced. This is because during the softening process, the hydrogen bond and ether linkage between lignin and hemicellulose was broken, which caused some lignin and hemicellulose to be dissolved and removed.…”
Section: Resultsmentioning
confidence: 92%
“…Previous works have demonstrated that by tuning the starting wood materials or the chemical processing parameters 31 , 32 , some blurred wood patterns can be maintained in the final products. It remains challenging to achieve clear and designable aesthetic patterns in transparent wood with integrated advantageous features such as a high optical transmittance, UV-blocking capability, low thermal conductivity and high mechanical strength.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, cellulose and hemicellulose are colorless substances with a simple structure. Relatively speaking, the structure of lignin is relatively complicated [28], which is also one of the main factors for bamboo coloration [29].…”
Section: Lignin Content Testingmentioning
confidence: 99%